Pengaruh Isometric Handgrip Exercises Terhadap Perubahan Tekanan Darah Pada Penderita Hipertensi: Literatur Review - Sari, Adjeng Pradita; Muhlisin, Abi (Jurnal Ners, 2024)
Hypertension is better known as the silent killer which is usually interpreted as hypertension which causes death without any symptoms. Physical activity that helps sufferers to lower blood pressure is by doing isometric handgrip exercises. The study aims is to analyze and identify changes in blood pressure during isometric handgrip exercises. The method used is Literature Review. The database used to search for this article is Science Direct, PubMed, and Google Scholar which were published in 2013-2023. The keywords used were "Isometric Handgrip", "Blood Pressure", and "Hypertension". The search results obtained 502 articles and 10 articles that met the selection criteria were selected. The results of the article show that as many as 9 out of 10 articles explain that isometric handgrip exercises can reduce blood pressure. The findings of the article show that isometric handgrip exercises can reduce blood pressure, so they can be used as additional interventions in the field of nursing.